Prevalensi Dan Faktor Risiko Ringworm Pada Sapi Bali Di Desa Baumata Timur - Marianus Triyanto Sado; Yohanes T.R.M.R Simarmata; Maxs U.E Sanam (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
One of the skin diseases in Bali cattle (Bos sondaicus) is ringworm which is caused by a fungus which has 3 genera, namely, Microsporus, Trichophyton and Epidermophyton which infect keratinized tissues such as skin, nails, and hair. This study aims to identify, determine the prevalence and determine the relationship between risk factors and prevalence of ringworm in bali cattle in Baumata Timur Village, Taebenu District, Kupang Regency. The relationship between risk factors and prevalence according to statistical data analysis using SPSS 2016 which is p≤0.05 and OR≥1 is declared to have a cause-and-effect relationship. Initial examination of the use of wood lamps was carried out on 53 bali cattle. The results of the examination using a wood lamp got 8 positive ringworm tails and skin scraping was carried out on the 8 samples. The sample was then isolated on SDA media (Sabouraud Dextrose Agar) at 25 degrees for 3-4 days and then examined under a microscope after being given a solution of lactophenol cotton blue. The results showed the presence of ringworm in Bali cattle with morphological characteristics that were identified as Trichophyton verucosum and the prevalence rate of ringworm in Bali cattle in East Baumata Village was 11.32%. Results Based on the research, there is no known significant relationship between risk factors and ringworm prevalence.